Phlebotomines in an area of the transmission of American cutaneous leishmaniasis in the north of Parana State, Brazil: Seasonal Variation and Nocturnal Activity - Teodoro, Ueslei; La Salvia Filho, Vicente; Lima, Edson Mauricio de; Spinosa, Roberto Palma; Barbosa, Orlando Carlos; Ferreira, Maria Eugênia Moreira Costa; Silveira, Thaís Gomes Verzignassi (Revista de Saúde Pública, 1993)
In two years of phlebotomine captures in a modified forest an appreciable decrease in the size of this insect population has been observed when compared to previous data from the same locality. The captures with the Shannon light trap were made in the outlying forest of Palmital farm in Terra Boa county, Parana State, Brazil. The predominant species were Lutzomyia withmani, Lutzomyia migonei, Lutzomyia intermedius e Lutzomyia fischeri. These insects were active from 6 p.m. to 6 a.m. and the period of greatest activity varied according to the species. These species' densities were higher in the summer and autum months. Environmental modifications may have influenced the observed changes in phlebotomine behavior.